Evaluation of Antiinflammatory and Analgesic Activity of Ixora coccinea Flower Extract - Bhattacharya, A.; Kar, D.R.; Sengupta, A.; Ghosh, G.; Mishra, S.K. (Asian Journal of Chemistry, 2011)
The antiinflammatory and analgesic activity of methanolic flower extract of Ixora coccinea Linn. Rubiaceae was investigated in this study. The effect of methanolic flower extract of Ixora coccinea was studied using carrageenan induced paw edema, acetic acid induced writhing response and hot plate method for studying antiinflammatory and analgesic activity. The extract at the dose levels of 200 and 400 mg/kg body weight significantly reduces (P<0.05) carrageenan induced inflammation in rats and shows analgesic activity, as determined by acetic acid induced writhing response and hot plate method. The effect of methanolic flower extract showed dose dependent reduction in the number of writhing as compared to control drug, which was highly significant. The percentage inflammation protection of methanolic flower extract at 400 and 200 mg/kg was found to be 80.14 and 68.26, which were very close to the standard drug (83.86).